Onset of Glycemic and Weight Outcomes in Patients Initiating Exenatide Once Weekly: The Relationship of Exenatide Exposure with Efficacy over the First 24 Weeks of Treatment - Blevins, Thomas (Diabetes Ther, 2016)
INTRODUCTION: Exenatide is gradually released from exenatide once weekly (QW) microspheres, and at steady state, consistently controls glycated hemoglobin (HbA1c) in patients with type 2 diabetes (T2D). This post hoc analysis examined the timing to onset of clinical responses and their correlations with exenatide concentrations after initiation of exenatide QW in patients with T2D. METHODS: Trial data were retrospectively analyzed to explore the early clinical responses to exenatide QW, including the relationship of exenatide concentration with its effects on efficacy [fasting plasma glucose (FPG), HbA1c, and body weight] and tolerability (nausea and vomiting). Exenatide QW efficacy and tolerability data were from DURATION-5, a 24-week, randomized, comparator-controlled trial [intent-to-treat (ITT) population]. Exenatide concentrations were measured in a patient subset (pharmacokinetic population). RESULTS: In the ITT (n = 129)/pharmacokinetic (n = 72) populations, baseline FPG, HbA1c, and body weight were 173/173 mg/dL, 8.5%/8.4%, and 97/98 kg, respectively. Exenatide concentrations gradually increased until reaching steady state at week 8. By week 4, the FPG reduction (−32.4 mg/dL) was 94% of the week 24 reduction (−34.6 mg/dL). Reductions in HbA1c began by week 4 (−0.6%) and stabilized by week 14 (week 24: −1.6%). Weight reduction at week 4 was −0.7 kg and decreased further (week 24: −2.3 kg). Peak nausea (7.2%) and vomiting (2.4%) occurred at weeks 6–8, declining thereafter. CONCLUSION: Clinically relevant responses to exenatide QW were evident by week 4, after exenatide concentration passed the therapeutic threshold but before steady state was achieved. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT00877890. FUNDING: AstraZeneca.